Moderation of celebrity worship groups in hijab and non-hijab on the impact of celebrity worship on the tendency of muslim dressstyle - Sekarayu Puspita Sari; Aprilia Mega Rosdiana (Journal of Indonesian Psychological Science (JIPS), 2022)
Celebrity Worship is a reflection of the development of appreciation and deeper enthusiasm for individuals or certain individuals or for their talents. There are several impacts on Celebrity Worship behavior. One of the impacts is a lifestyle, especially a dress style. Changes in dress style have also occurred among some alumni of pesantren Daarul Qur'an Putri Cikarang. The change in dress style also depends on who the celebrity is followed by the individual. The aim of this study is to determine how different the impact of celebrity worship is on the tendency of Muslim dress styles in groups that idolize celebrities in hijab versus non-hijab celebrity idol groups. This research was quantitative research with a questionnaire Likert scale. The sampling was using purposive sampling. The subjects were 84 alumni divided into groups. The data was analyzed using moderation analysis by moderating the variables of the group. The results of this study showed that there were differences in the direction of the impact of both groups. In the hijab group, there was a positive impact and in the non-hijab idol group, there was a negative impact. Celebrity Worship merupakan suatu pencerminan pengembangan apresiasi serta antusiasme yang lebih dalam terhadap individu atau beberapa individu tertentu ataupun terhadap bakat mereka. Terdapat beberapa dampak dari perilaku Celebrity Worship salah satunya adalah gaya hidup terutama gaya berbusana. Perubahan gaya berbusana juga terjadi pada beberapa alumni pondok pesantren Daarul Qur’an Putri Cikarang. Perubahan gaya berbusana tersebut juga tergantung dari siapakah selebriti yang diikuti oleh individu tersebut. Penelitian ini bertujuan melihat bagaimana perbedaan pengaruh celebrity worship terhadap kecenderungan gaya berbusana muslimah pada kelompok yang mengidolakan selebriti berhijab dan kelompok pengidola selebriti nonhijab. Penelitian ini merupakan penelitian kuantitatif dengan quetioner Skala Likert. Pengambilan sampel menggunakan purposive sampling. Subjek sebanyak 84 alumni yang dibagi menjadi kelompok. Data dianalisa menggunakan analisa moderasi dengan memoderasikan variabel kelompok. Hasil penelitian ini terdapat perbedaan arah pengaruh dari kedua kelompok. Pada kelompok berhijab terdapat pengaruh positif dan pada kelompok pengidola non hijab terdapat pengaruh negatif. Dari penelitian ini menunjukkan pentingnya memiliki nilai-nilai karakter positif sebagai dasar bagi individu untuk mempertimbangkan hal-hal eksternal yang dapat mempengaruhi gaya hidupnya, terutama gaya berpakaiannya